Peningkatan Kualitas Lahan Menggunakan Pupuk Organik Untuk Pertanian Berkelanjutan - Arief Budiyanto; Ishak Juarsah; Etik Puji Handayani (Jurnal WACANA PERTANIAN, 2020)
Using organic fertilizer as a soil conditioner can increase the C-organic content in the soil. Nutrient content of organic fertilizers include (1) Contains nutrients in types and quantities varying depending on the origin, (2) providing nutrients in a slow (slow release) and in limited quantities, and (3) has the main function to improve fertility and soil health. Organic fertilizers derived from manure are the best soil ameliorants compared to other aminators. Nutrients contained in organic fertilizers are generally low and very varied. As soil amendment material, organic fertilizer helps in preventing erosion and reducing soil cracks. Organic matter as soil enhancers can improve soil physical, chemical and biological properties.